Aberrant localization of apoptosis protease activating factor-1 in lipid raft sub-domains of diffuse large B cell lymphomas - Hirpara, J.; Loh, T.; Ng, S.; Chng, W.; Pervaiz, Shazib (Impact Journals LLC, 2016)
Resistance to chemotherapy remains a challenge in the clinical management of diffuse B cell lymphomas despite aggressive chemotherapy such as CHOP and monoclonal CD20. Here we provide evidence that the apoptosome adaptor protein, Apaf-1, is mislocalized in primary cells derived from patients with diffuse large B cell lymphomas (DLBCL). Whereas, the total expression of Apaf-1 did not change, its subcellular localization was significantly different in DLBCL, compared to T cell lymphomas as well as cells derived from reactive lymphadenopathy biopsies. As expected, Apaf-1 was detected in the cytosolic fractions of non-B cell lymphomas and non-cancerous tissues; however, in B cell derived lymphomas the protein was detected in membrane raft sub-domains rather than the cytosol. Disruption of lipid raft structures resulted in the redistribution of Apaf-1 to the cytosol and restored apoptosis sensitivity of DLBCL. Furthermore, we identified novel small molecule compounds that target DLBCL by promoting Apaf-1 release form lipid rafts via mechanisms that involve an increase in intracellular reactive oxygen species production. Taken together, our results implicate Apaf-1 mislocalization as a potential diagnostic and prognostic marker for DLBCL, and provide a novel therapeutic strategy for circumventing the drug refractory nature of this sub-class of B cell lymphoma.